Massive Pneumoureter and Pneumobladder in the Context of Emphysematous Pyelitis - Patil, Santosh; Kundargi, Vinay S.; Patil, Siddanagouda B.; Vaidya, Manoj K. (Achievements and Challenges of Medicine and Medical Science Vol. 6, 2024)
Emphysematous urinary tract infections are necrotising infections caused by gas-forming uropathogens. High levels of glucose in the tissue act as a substrate for bacteria such as E.coli (>50%), Klebsiella(21%) and Proteus spp. which in turn ferment the sugars to produce carbon dioxide. Emphysematous pyelitis refers to the collection of gas in the renal collecting system. Although gas is encountered in the pelvicalyceal system, it is quite rare to find a massive accumulation of gas in the ureter and urinary bladder. This is an interesting case of a middle-aged diabetic male who presented with flank pain and lower urinary tract symptoms and his evaluation revealed a massive right pneumo-ureter and pneumo-bladder. Prompt evaluation with computed tomography and early intervention in the form of DJ stenting and catheterisation helped to resolve the massive air pockets in the ureter and the bladder.